Evidence that the superoxide-generating system of human leukocytes is associated with the cell surface. - Goldstein, I M (1977)
Superoxide anion (O-2-) generation by human peripheral blood polymorphonuclear leukocytes is enhanced when these cells encounter appropriate soluble or particulate stimuli. O-2- generation requires intact, viable cells and proceeds independently of phagocytosis. To investigate the possibility that the O-2--generating system is associated with the outer surface of the polymorphonuclear leukocyte plasma membrane, we have examined the effects upon O-2- production of p-diazobenzenesulfonic acid, a reagent which can react predominantly with proteins of the external cell membrane. When normal human polymorphonuclear leukocytes were preincubated with cytochalasin B (to minimize endocytosis) and then exposed to the surface-active lectin, concanavalin A, the cells were stimulated to generate O-2- in a concentration- and time-dependent fashion and selectively to discharge the granule-associated enzyme, lysozyme, into the surrounding medium. These responses, as well as cellular binding of [H] concanavalin A, could be blocked by alpha-methyl-D-mannoside. Brief treatment (less than 5 min at 4 degrees C) of the cells with p-diazobenzenesulfonic acid (1.0-5.0 mM) significantly interfered with concanavalin A-mediated O-2- generation but had no influence upon lysozyme release or upon binding of [3H] concanavalin A. The diazonium salt did not alter cell viability or the specific activity of the cytoplasmic enzyme, lactate dehydrogenase (inhibitable under conditions which allowed entry of this reagent into the cytosol). p-Diazobenzenesulfonic acid, therefore, very likely exerted its effects at the cell surface of the intact polymorphonuclear leukocyte, selectively inhibiting O-2- production (either directly or indirectly) without influencing another response to lectin-cell contact: release of lysozyme. These results support the possibility that a polymorphonuclear leukocyte ectoenzyme is responsible for O-2- production.